The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.17219/acem/67760
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary estimation of tissue factor pathway inhibitor (TFPI) and protein C in patients with intracranial tumors

Abstract: Background. In patients with intracranial tumors, hypercoagulability is observed due to brain tissue and tumor cells being the source of tissue factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…A majority of our intracranial patient population underwent free flap cranial reconstruction after meningioma resection. Meningiomas, despite not containing glial tissue, have been found to exhibit similarly increased levels of TF as intraparenchymal tumors 30 . Ishimaru et al found the level of TF expression to correlate with the proliferative ability of a meningioma, with increased expression in higher grade tumors 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A majority of our intracranial patient population underwent free flap cranial reconstruction after meningioma resection. Meningiomas, despite not containing glial tissue, have been found to exhibit similarly increased levels of TF as intraparenchymal tumors 30 . Ishimaru et al found the level of TF expression to correlate with the proliferative ability of a meningioma, with increased expression in higher grade tumors 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Meningiomas, despite not containing glial tissue, have been found to exhibit similarly increased levels of TF as intraparenchymal tumors. 30 Ishimaru et al found the level of TF expression to correlate with the proliferative ability of a meningioma, with increased expression in higher grade tumors. 28 Similar to intraparenchymal tumor resection, D dimer, and fibrin degradation levels have been reported to rise during meningioma surgery.…”
Section: Discussionmentioning
confidence: 99%